The underestimated role of the sports psychiatrist in athletic performance restoration, maintenance, and enhancement in sports - Claussen, Malte Christian; Burger, James W.; Menon, Ranjit; Nishida, Masaki; Koh Boon Yau, Eugene; Nahman, Carolyn; Whitehead, Jim; Edwards, Carla; Baron, David; Glick, Ira (John Wiley and Sons, 2024)
In competitive and elite sports, mental health and athletic performance cannot be considered separately. Mental disorders in sports are bidirectionally associated with reduced athletic performance. A decline in performance, both within and outside of sport, can be a sign of mental disorder. Additionally, poor athletic performance is a potential risk factor for mental disorders in athletes. The central role sports psychiatrists play in the mental health of athletes is well-established. However, their role in athletic performance is less well-described and more controversial, perhaps due to a perception that performance is purely a secondary outcome of good mental health. This paper discusses the role that sports psychiatrists can play in athletic performance within competitive and elite sports. Performance can be distinguished into three key focus areas for sports psychiatrists: (i) performance restoration, (ii) performance maintenance, and (iii) performance enhancement. These should be considered throughout the continuum of mental health care, from prevention, treatment, to ongoing care for mental disorders. When reduced performance is due to a mental disorder, psychiatric treatment should purposefully aim to restore functioning and performance as part of management. Maintenance of performance is, similarly, an important element of the prevention, psychiatric treatment, and ongoing care of mental disorders. Holistic sports psychiatrists may also choose to aim for athletic performance enhancement beyond the context of mental health symptoms and disorders, to help athletes flourish and achieve their goals.